Krytyka nierzeczywistości w konserwatyzmie Carla Schmitta i Leo Straussa - Święcicki, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In this article I have tried to demonstrate that in both conservative thinkers one may find a belief in the unreal nature of today’s world which is either a realized utopia or utopia being realized. It is a world in which the situation of clarity about the most important issues is avoided, fundamental questions are repealed and the choice between the essential objectives of life is challenged. Relying on several early and late lesser-known or unknown works of both thinkers I present the specifics of their conservative criticism of unreality.
Keywords: Schmidt, Karl (1836–1888); Strauss, Leo; konserwatyzm; myśl polityczna; Niemcy